Islet Transplantation in the Lung via Endoscopic Aerosolization: Investigation of Feasibility, Islet Cluster Cell Vitality, and Structural Integrity - Lau, Hien (Cell Transplant, 2020)
Aerosolized drug delivery has recently attracted much attention as a possible new tool for the delivery of complex nanoparticles. This study aims to investigate whether catheter-based aerosolization of islets via endobronchial systems is a feasible option in islet transplantation. Besides investigating the feasibility of islet aerosolization, we also examined cluster cell vitality and structural integrity of the islets following aerosolization. Using an ex vivo postmortem swine model, porcine pancreatic islets were isolated and aerosolized with an endoscopic spray catheter. Following aerosolization, islet cell vitality and function were assessed via Calcein AM and propidium iodide as well as insulin production after glucose exposure. In the final step, the overall feasibility of the procedure and structural integrity of cells were analyzed and evaluated with respect to clinical applicability. No significant difference was detected in the viability of control islets (90.67 ± 2.19) vs aerosolized islets (90.68 ± 1.20). Similarly, there was no significant difference in control islets (1.62 ± 0.086) vs aerosolized islets (1.42 ± 0.11) regarding insulin release after stimulation. Indocyanine green marked islets were transplanted into the lung without major difficulty. Histological analysis confirmed retained structural integrity and predominant location in the alveolar cavity. Our ex vivo data suggest that catheter-based aerosolized islet cell delivery is a promising tool for the application of cell clusters. According to our data, islet cell clusters delivery is feasible from a mechanical and physical perspective. Moreover, cell vitality and structural integrity remain largely unaffected following aerosolization. These preliminary results are encouraging and represent a first step toward endoscopically assisted islet cell implantation in the lung.